2010
DOI: 10.1002/14651858.cd000174.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic intravenous indomethacin for preventing mortality and morbidity in preterm infants

Abstract: Prophylactic intravenous indomethacin for preventing mortality and morbidity in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
228
5
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(263 citation statements)
references
References 72 publications
13
228
5
17
Order By: Relevance
“…Prophylactic indomethacin may have short-term benefits for preterm infants including a reduction in the incidence of symptomatic PDA, PDA surgical ligation, and severe IVH [14]. From 2006, we routinely introduced indomethacin prophylaxis for preterm infants born at <25 weeks of GA to reduce the risk of intraventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic indomethacin may have short-term benefits for preterm infants including a reduction in the incidence of symptomatic PDA, PDA surgical ligation, and severe IVH [14]. From 2006, we routinely introduced indomethacin prophylaxis for preterm infants born at <25 weeks of GA to reduce the risk of intraventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…For indomethacin most studies have used 0.1 mg/kg/d for three doses. Meta-analysis results of prophylactic indomethacin use showed 50 % reduction of hsPDA, 35 % reduction in severe IVH (> grade2), and 50 % reduction in the need for surgical ligation of PDA, compared to placebo [32]. The trial of indomethacin prophylaxis in preterm infants (TIPP) also showed a reduction in early pulmonary hemorrhage.…”
Section: Prophylactic Therapymentioning
confidence: 98%
“…Antenatal corticosteroids are known to reduce the occurrence of patent ductus arteriosus and IVH. [41][42][43][55][56][57][58][59] Systematic reviews and meta-analyses of the studies of prophylactic postnatal indomethacin have confirmed the significant reduction in severe IVH. In 14 trials including over 2,500 newborns, a 35% reduction in severe IVH was evident (RR 0.66 [95% CI, 0.53-0.82], P,.001).…”
Section: The First Weekmentioning
confidence: 99%
“…In 14 trials including over 2,500 newborns, a 35% reduction in severe IVH was evident (RR 0.66 [95% CI, 0.53-0.82], P,.001). 58 However, a well-conducted study of prophylactic indomethacin did not show a benefit on neurodevelopmental outcomes, despite a reduction in severe IVH (Grades 3 and 4) from 13% to 9%. 59 The demonstrated reduction in severe IVH, serious pulmonary hemorrhage, and the need for surgical ligation of patent ductus arteriosus 59 may well be considered significant benefits by families.…”
Section: The First Weekmentioning
confidence: 99%